Ischiopubic and odontoid synchondrosis in a boy with progressive pseudorheumatoid chondrodysplasia - Ben Ghachem Maher; Ben Chehida Farid; Al Kaissi Ali; Grill Franz; Klaushofer Klaus (BMC, 2007)
Abstract Purpose To present the case of a 14-year-old boy with clinical and radiographic features of pseudorheumatoid chondrodyspalsia with additional, potentially serious, cervical malformations. Methods Detailed clinical and radiological examinations were undertaken with emphasis on the usefulness of 3D-CT scanning. Results There was synchondrosis between the odontoid and the body of the axis and the cephalad part of the odontoid was detached. Bilateral ischiopubic ossification defects and ischiopubic and odontoid synchondroses were additional abnormalities. 3D-CT scan showed an orthotopic type of os odontoideum associated with an occult axial fracture. Conclusion Children who are younger than seven years of age are predisposed to develop odontoid fracture. The latter occur because of the presence of physiological odontoid synchondrosis, but fractures can result from trivial injuries as well as from high-energy trauma. The persistence of an infantile odontoid, with a large pre-adulthood head in children with skeletal dysplasias, is a major risk factor for sudden death or significant morbidity. Comprehensive orthopaedic management must follow early identification of these malformations.